Short-term rentals as a new urban frontier: evidence from European cities - Cocola-Gant, Agustín (2021)
Papers in this special issue offer a wide range of political economy and sociological perspectives to explain the development and impacts of short-term rentals (STRs) in European cities. Empirically, they provide insights regarding STR providers, socio-spatial impacts, and regulation. Authors reveal the professionalization of the sector vis-à-vis the connection between STRs and the wider financialization of housing. STRs are predominantly supplied by professional property managers as well as by middle-class individuals for which renting on digital platforms is their main professional activity. Furthermore, the increasing professionalization of hosts and the intrinsic competition among them is largely stimulated by the business model of digital platforms which has progressively favoured professional operators. Understanding how STRs are shaped by platform capitalism helps to explain the socio-spatial impacts of this market as well as why current regulations have not mitigated such impacts. In terms of impacts, contributions to this special issue document processes of displacement, gentrification, and how the penetration of visitors in neighbourhoods is experienced by residents as a process of loss and dispossession. However, due to the lobbying campaigns of professional operators and industry players, regulation has led to the legitimization of this new market rather than to the limitation of the activity. Therefore, the special issue challenges the use of a ‘sharing economy' and ‘peer-to-peer platforms’ as analytical categories, and, instead, provides evidence of why the STR market should be seen as part of the wider expansion of platform capitalism, consolidating the neoliberal and financialized urban paradigm.